All-terrain vehicle serious injuries and death in children and youth: A national survey of Canadian paediatricians. Issue 1 (18th June 2018) - Gill, Peter J; McLaughlin, Thomas; Rosenfield, Daniel; Moore Hepburn, Charlotte; Yanchar, Natalie L; Beno, Suzanne
Abstract: Background: All-Terrain Vehicles (ATVs) are a leading cause of serious injury in children and youth. Certain Canadian regions have implemented legislation to promote safety, including age restrictions, mandatory training and helmet use. Jurisdictions with more stringent ATV safety legislation have been shown to have reduced injury rates in the short term. Objectives: To estimate the burden of ATV-related serious injury and death in Canada and to identify Canadian physicians' knowledge of ATV-related legislation, safety and health promotion practices. Methods: A one-time survey was distributed to practicing paediatricians and paediatric subspecialists participating in the Canadian Paediatric Surveillance Program (CPSP) in October 2016. Results: Of 2793 physicians contacted, 904 responded (32.4%). There were 181 reported cases of serious and/or fatal ATV-related injuries, including 6 deaths. Children aged 10 to 14 represented the most number of cases (n=82, 45.3%), followed by 15 to 19 (n=48, 26.5%) and 5 to 9 (n=40, 22.1%). Most cases occurred in July/August (48.3%) and May/June (25.2%), were in males (n=133, 78.2%), and occurred during recreational activity (n=139, 83.2%) or organized racing (n=6, 3.6%). In 99 cases (58.9%), the child was the driver of the ATV. Only two-thirds of respondents (67.5%) knew that ATVs should not carry passengers while under half (42.2%) never discussed ATV safety with their patients. Conclusions: ATV-related injuries and deaths in Canadian children remain a serious public health problem. Education of health care practitioners, including paediatricians, is needed to promote safety. Despite efforts to reduce ATV-related injuries, there remains a significant number of serious injuries and/deaths related to their use.